Comparison of Breast Biopsy Pathology Reporting with Breast Imaging Reporting and Data System (Bi-Rads) Categories-An Institutional Study - Humayun, Saba; Asif, Muhammad; Khadim, Muhammad Tahir; Din, Hafeez Ud; Anwar, Madeeha; Rashid, Farhat (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine concordance and discordance between radiological and pathological findings of palpable breast lesions.Study Design: Comparative cross-sectional study.Place and Duration of Study: Department of Histopathology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Oct 2018 to Mar 2019.Methodology: Imaging and histopathologic reports of a total of 170 female patients with breast lumps were analyzed. Concordance and discordance rates were estimated by comparing histopathology and imaging findings. All the reports were divided into four categories. Malignant concordant lesions showed malignant features and benign concordant lesions showed benign features on both imaging and histopathology. Malignant discordant lesions were those lesions, which were reported benign on imaging but proved to be malignant on histopathology and benign discordant lesions were those showing malignant features on imaging but turned out to be benign on histopathology.Results: Overall concordance was observed in 138 (81.2%) cases with a discordance rate of 18.8% (15.3% benign discordant and 3.5% malignant discordant). All malignant discordant cases (n=6, 3.5%) were reported as Breast Imaging Reporting and Data System category III on imaging and all came out to be invasive ductal carcinoma on histopathology. All benign discordant cases (n=26, 15.3%) were reported as Breast Imaging Reporting and Data System category IV on imaging.Conclusion: A higher discordance rate between imaging and histopathologic findings was observed in the present study as compared to what cited in the literature. Discordant cases should be followed by repeat biopsy for confirmation of diagnosis